Students’ acceptance using facebook as a learning tool: a case study - S.M. Mali, Alaa; Syed Hassan, Sharifah Sariah (Asian Economic and Social Society, 2013)
With the advancement of technology in communication, social networks are widely used not only for connecting friends and social community but also as a means for learning. Previous research have focussed on Facebook related to teaching and learning (Bosch, 2009); college students experiences (Pempek, et al, 2009) and using Facebook for e-portfolio among higher learning students (Raja Hussein & Ng, 2010). This paper aimed to investigate the level of acceptance of using Facebook as a learning tool among students in a Public University in Kuala Lumpur. The design of this study was a triangulation of quantitative and qualitative methods. A self-constructed questionnaire with (25) items was used to measure the perceived ease of use, perceived usefulness and students’ attitude toward using Facebook as a learning tool. The survey was carried out to a purposive sampling where only students who used Facebook in learning were selected. Thus, the questionnaires were distributed to 100 students in one of the faculties in International Islamic university Malaysia IIUM. Three students were selected for the interviews. The results of this study show that only 77 respondents responded to the questionnaires. The findings indicate that there was no significant difference between male and female in their intention to use Facebook as a learning tool. On the other hand, ease of use of Facebook as a learning tool and its usefulness were significantly affected intention to use Facebook. Further enhancement of the quantitative finding was supported from the interviews where challenges and barriers are discussed.